New Alkaloids from the Mediterranean Sponge Hamigera hamigera - Wafaa Hassan; RuAngelie Edrada; Rainer Ebel; Victor Wray; Peter Proksch (Marine Drugs, 2004)
Abstract: The Mediterranean sponge Hamigera hamigera (family Anchinoideae) was studied since its total extract showed deterrent activity in a fish feeding assay. Eight compounds were isolated from the biologically active fractions and four of these proved to be new natural products, hamigeroxalamic acid (1), hamigeramine (2), hamigeramide (3) and hamiguanosinol (5). The structures of the new compounds were elucidated by 1D and 2D NMR spectroscopy and mass spectrometry .